Sistematik Review: Kemasan Ramah Lingkungan dalam Mendukung Keberlanjutan Industri dan mengurangi dampak lingkungan - Sarlin (Jurnal Sains dan Pendidikan Biologi, 2023)
Eco-friendly packaging has become a major focus in efforts to support industry sustainability and reduce environmental impact. This systematic review aims to investigate various studies and research related to the development of environmentally friendly packaging and its impact on the environment. Conventional packaging using non-environmentally friendly materials, especially plastic, has caused serious problems for global environmental sustainability, including ocean pollution, ecosystem damage, and human health problems. This study aims to see whether environmentally friendly packaging provides solutions to industrial sustainability and reduces environmental impacts. The results of this systematic review indicate that the adoption of environmentally friendly packaging can provide significant benefits towards reducing environmental impacts compared to conventional packaging. Alternative raw materials such as bioplastics, recycled paper and recycled raw materials have been shown to reduce carbon footprints and minimize the accumulation of plastic waste in the environment. In addition, innovative packaging design and efficiency in the production process also play an important role in maximizing sustainability benefits. In conclusion, this systematic review provides strong evidence that the development of environmentally friendly packaging can be an effective solution in supporting industrial sustainability and reducing negative impacts on the environment. The next steps are to strengthen collaboration between industry stakeholders, academics, government and consumers to encourage innovation and implementation of broader and more sustainable eco-friendly packaging.